SSR Marker-Based Genetic Resource Assessment of the Rainbow Clam Moerella iridescens Along the Coasts of China: Implications for Strategy of Conservation Management - Li, Xiaoying; Gao, Shan; Zhao, Manman; Dong, Zhiguo (Frontiers in Marine Science, 2022)
This study aims to determine the genetic structure of rainbow clam Moerella iridescens in different sea areas of China. Seventeen pairs of microsatellite primers (SSR) were used to amplify the SSRs of rainbow clam in Lianyungang of Haizhou Bay, Chongming of Shanghai, Ningde of Fujian, Daishan of Zhoushan, and Cixi and Wenzhou of Zhejiang. A total of 1,146 alleles were detected in 310 individuals from the 17 SSR loci. The average observed heterozygosity of six populations was 0.4381−0.6139, the average expected heterozygosity was 0.5897−0.7325, and the average Shannon diversity index was 1.2655−1.7998. The clams exhibited rich genetic diversity, and the FST of the genetic differentiation index of the six populations was 0.0470, indicating low genetic differentiation among the populations. The results indicated that rainbow clams along the coasts of China exhibited high diversity and low population differentiation.